ANALYSIS OF COMMUNITY SATISFACTION ON TOURISM SERVICES INTEGRATED SERVICES (POSYANDU) IN LOMPO RIAJA KELURAHAN, TANETE RIAJA DISTRICT, BARRU REGENCY - Arnis; Nurlia (P3M Stia Al Gazali Barru and Meraja media, 2022)
Copyright (c) 2022 Meraja journal